Nitrogen mineralization rates in soils amended with different poultry manures - MARTÍN, JOSÉ V; IMPERIAL, R MIRALLES DE; CALVO, R; DELGADO, M M (The Indian Journal of Agricultural Sciences, 2014)
The Nitrogen (N) availability from field-applied poultry manure for crop production is influenced by a number of complex processes. Keeping these in view, an experiment was conducted to evaluate the decomposition of poultry manure by analysing the nitrogen mineralization. Thus the rate and timing of PM applications need to consider the N requirements of the given crop to ensure the efficient use of these products.